The widest broadband transmission spectrum (0.38-1.71 μm) of HD 189733b from ground-based chromatic Rossiter-McLaughlin observations - Oshagh, Mahmoudreza; Bauer, F. F.; Lafarga, M.; Molaverdikhani, Karan; Amado, P. J.; Nortmann, L.; Reiners, A.; Guzmán-Mesa, A.; Pallé, E.; Nagel, E.; Caballero, J. A.; Casasayas-Barris, N.; et al. (Astronomy and astrophysics, 2020)
Multiband photometric transit observations (spectro-photometric) have been used mostly so far to retrieve broadband transmission spectra of transiting exoplanets in order to study their atmospheres. An alternative method was proposed, and has only been used once, to recover broadband transmission spectra using chromatic Rossiter-McLaughlin observations. We use the chromatic Rossiter-McLaughlin technique on archival and new observational data obtained with the HARPS and CARMENES instruments to retrieve transmission spectra of HD 189733b. The combined results cover the widest retrieved broadband transmission spectrum of an exoplanet obtained from ground-based observation. Our retrieved spectrum in the visible wavelength range shows the signature of a hazy atmosphere, and also includes an indication for the presence of sodium and potassium. These findings all agree with previous studies. The combined visible and near-infrared transmission spectrum exhibits a strong steep slope that may have several origins, such as a super-Rayleigh slope in the atmosphere of HD 189733b, an unknown systematic instrumental offset between the visible and near-infrared, or a strong stellar activity contamination. The host star is indeed known to be very active and might easily generate spurious features in the retrieved transmission spectra. Using our CARMENES observations, we assessed this scenario and place an informative constraint on some properties of the active regions of HD 189733. We demonstrate that the presence of starspots on HD 189733 can easily explain our observed strong slope in the broadband transmission spectrum.
Gesehen am 22.04.2021